2012
DOI: 10.1152/ajpgi.00462.2011
|View full text |Cite
|
Sign up to set email alerts
|

Impaired ghrelin signaling is associated with gastrointestinal dysmotility in rats with gastroesophageal reflux disease

Abstract: Gastroesophageal reflux disease (GERD) is often associated with decreased upper gastrointestinal motility, and ghrelin is an appetite-stimulating hormone known to increase gastrointestinal motility. We investigated whether ghrelin signaling is impaired in rats with GERD and studied its involvement in upper gastrointestinal motility. GERD was induced surgically in Wistar rats. Rats were injected intravenously with ghrelin (3 nmol/ rat), after which gastric emptying, food intake, gastroduodenal motility, and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…Ghrelin is expressed by GHRL gene, several SNP are informed for it. In literature is actively studied the SNP allele polymorphism with obesity [10,11], food behavior disorders [12] and metabolism disturbances [13], and also with gastric acid secretion [14] and fast stomach emptying [15,16]. Mutations in this gene can cause low levels of ghrelin, registered at obesity [17].…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin is expressed by GHRL gene, several SNP are informed for it. In literature is actively studied the SNP allele polymorphism with obesity [10,11], food behavior disorders [12] and metabolism disturbances [13], and also with gastric acid secretion [14] and fast stomach emptying [15,16]. Mutations in this gene can cause low levels of ghrelin, registered at obesity [17].…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of the cardiac sling fibers have also been correlated with a decrease in LES tone. Nahata et al proposed the concept that impaired ghrelin signaling as predisposing patients to GERD after sleeve gastrectomy [29]. The routine repair of small hiatal hernias may contribute to LES dysfunction by disrupting the normal anatomical barriers to reflux in order to perform the repair.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin increases food intake and suppresses energy expenditure [3, 11]. In our previous study, we used GERD rats to demonstrate lack of responsiveness through an acute bolus administration of ghrelin (3 nmol/rat) [12]. In comparison with sham-operated rats, the growth hormone secretory effect in GERD rats intravenously administered acyl ghrelin decreased, and acute administration of acyl ghrelin did not suppress the decrease in food intake, gastric emptying, or gastric motility.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated administration of acyl ghrelin (3 nmol/rat/day) to GERD rats had no effect on food intake or body weight throughout the experiment in this study. We previously demonstrated that acute intravenous administration of acyl ghrelin at a dose of 3 nmol/rat to sham-operated rats increased food intake significantly [12]. In normal rats, administration of ghrelin at a dose of 1.5 nmol/rat also increased food intake significantly [13].…”
Section: Discussionmentioning
confidence: 99%